Sosialisasi dan Pelatihan Pembuatan Face Mask Sebagai Upaya Pencegahan Penularan Covid-19 di Desa Sidoharjo Tanjunganom Nganjuk - Sri Wahyunik; Nur Rulifatur Rohmah; Rakhil Fajrin (Janaka, Jurnal Pengabdian Masyarakat, 2021)
The pandemic has an impact on the world of economy, society and education. The problems that occur in the Jajar hamlet community are a lack of understanding of the dangers of COVID-19 and non-compliance with health protocols. TPQ Al-Khodijah and the Al-Falah mosque are active assistance partners in religious activities, but they have not implemented health protocols as an effort to prevent the spread of COVID-19. Efforts are being made to conduct socialization and training on making face masks (in the form of masks and face shields) with the aim that they can adopt healthy living habits by using masks and can make face masks that are economical and environmentally friendly independently. The approach used is Asset Based Community Development (ABCD) and uses the service learning method. The importance of knowledge of the dangers of COVID-19 and how to prevent it as a pillar to make the general public aware of the dangers of COVID-19 and adhere to health protocols during this pandemic, so that people are safe even though they have to live side by side with Covid-19 in an unpredictable period.